FRECUENCIA DE B-LACTÁMICOS Y TETRACICLINAS EN LECHE FRESCA EN LA CUENCA DE AREQUIPA - Ortiz Z., César (2008)
The objective of the present study was to evaluate the frequency of ?-lactams and tetracyclines in raw milk samples contaminated with antibiotics in the dairy area of Arequipa. A total of 616 milk samples were collected in October 2007, and 99 of them were contaminated with antibiotics. Among them, the frequency of samples containing ? - lactams and tetracyclines was 88.8 and 61.6% respectively. The number of samples contaminated with b-lactams was statistically higher as compared to those contaminated with tetracyclines (p<0.01). The study showed that antibiotics belonging to the ?-lactams group are an important source of contamination of milk in the dairy area of Arequipa.